A brief video-coaching intervention buffers young children's vulnerability to the impact of caregivers' depressive symptoms: Examination of differential susceptibility. (December 2021) - Liu, Sihong; Fisher, Philip A.; Schlueter, Lisa J.; Phu, Tiffany; Gunnar, Megan R.; Watamura, Sarah E.
Abstract: Informed by the National Institute of Mental Health's Research Domain Criteria (RDoC) and developmental psychopathology frameworks, the current study used cortisol area under the curve with respect to ground (AUCg) as an index of differential sensitivity to context, which was expected to predispose young children with elevated vulnerability to adverse caregiving experiences and adaptive sensitivity to intervention effects. Particularly, the study aimed to determine whether improving caregivers' responsive parenting through the Filming Interactions to Nurture Development (FIND) intervention would buffer children's biologically embedded vulnerability to caregivers' depressive symptoms. Data were derived from a randomized controlled trial using pretest–posttest design with low-income families of children aged 4 to 36 months ( N = 91). Young children's differential sensitivity was measured using cortisol AUCg during a structured stress paradigm. As hypothesized, children whose cortisol AUCg indicated greater sensitivity to social context exhibited more internalizing and externalizing behaviors in relation to caregivers' elevated depressive symptoms. Critically, the intervention program was effective in attenuating psychopathology symptoms among the more biologically sensitive children. As proven by rigorous statistical tests, the findings of this study partially supported the differential susceptibility hypotheses, indicating both greater vulnerability to adverse conditions and responsiveness to intervention among children with high levels of cortisol AUCg.